ANALISIS MARGIN PEMASARAN KOPRA DI DESA SIBOANG KECAMATAN SOJOL KABUPATEN DONGGALA - Fikmal Fikmal; Sulmi Sulmi (Universitas Tadulako, 2022)
This study aims to analyze the copra marketing chain from Siboang Village, Sojol District, Donggala Regency to the hands of consumers. This research was conducted in Siboang Village, Sojol District, Donggala Regency from July to September 2020. Respondents were determined using simple random sampling method (Simple Random Sampling) with 32 producers (farmers) as selected by means of the Tracing Sampling method in order to obtain 1 treder and 1 wholesaler. Marketing show thet the copra marketing channel in Siboang Village is through two marketing channels namely: Farmers Trader, Collectors, Factory wholesaler (final concumers), Farmers, Factory wholesaler (final concumers). Theresults of channel 1 copra marketing margin analysis, namely MT = Rp. 2,000/kg while the second channels is MT = Rp. 1,000/kg. The share of the price received by copra farmers on channel 1 is 75.00%, while in the second channel is 87.5%. Marketing efficiency in the first channel is 9.85%, while the efficiency value for channel II is 8.58%, so that of the two channels, the most efficient channel is the second channel with an efficiency value of 8.58%.